Adaptation of a human gut epithelial model in relation to the assessment of clinical pharmacokinetic parameters for selected tyrosine kinase inhibitors - Richard Honeywell; Christien Fatmawati; Marita Buddha; Sarina Hitzerd; Ietje Kathman; Godefridus Peters (ADMET and DMPK, 2015)
The absorption, efflux and transport properties of two of the most commonly used tyrosine kinase inhibitors (TKIs), Erlotinib (E) and Gefitinib (G) were investigated using an adapted workable methodology of a 3-day Caco-2 cell monolayer transwell system, a standard model to test drug permeability and uptake of orally administered compounds.  Monolayer integrity was tested using trans-epithelial electrical resistance (TEER) measurements, while drug concentrations were determined with a validated LC-MS/ MS technique. Addition of 5 % bovine serum albumin (BSA) maintained drug concentrations at  20 µM through the avoidance of chelate formation, (nevertheless, a reduced accumulative mass transport of the protein bound drug was observed). Investigation with Ko143 (a specific blocker of ABCG2) or NaN3 (a metabolic inhibitor) indicated an interplay between active transport and passive diffusion for gefitinib, while active transport proved to be absent for erlotinib (p < 0.05). The mechanism indicates that ABCG2 is partially involved with accumulation of gefitinib in the cell. This adapted methodology is well suited for absorption, efflux and transport studies and may be extended to investigate the dominant mechanism involved in the transport of TKIs.